The Influence of the Problem Based Learning Model Assisted by the Firing Line on Critical Thingking Skills in the Science Subject of 4th Grade Emlementary School Students - Hasanah, Fina Nessa; Mayarni, Mayarni (Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 2024)
The research at this time aims to analyze the ability of each student in the type of critical thinking by using a problem-based learning model supported by the firing line. The research method used is a quantitative research approach with a pretest-posttest research design of non-equivalent control group design. There are 31 students who are declared as the experimental class while for 31 students who will be the control class will be randomly selected. In this study using an instrument containing 12 essay questions. The final result of this study shows the paired-sample t-test analysis that the significance value (two-tailed) is 0.000, which is less than 0.05. In addition, the N-gain test displays the average of the N-gain for the experimental class which is 0.7490 can be categorized as "high", and for the control class N-gain which is 0.6522 can be categorized as "medium". Therefore, the conclusion from the explanation above is that there is an increase in students' critical thinking skills, namely the acceptance of the hypothesis when applying a problem-solving-based learning model with the help of the firing line in IPAS learning for grade 4th elementary school students, in other words, the hypothesis is accepted.